1979
DOI: 10.1073/pnas.76.1.256
|View full text |Cite
|
Sign up to set email alerts
|

Conformational properties of the acetylcholine receptor as revealed by studies with constrained depolarizing ligands

Abstract: Conformational aspects of the acetyicholine receptor (AcChoR) of Electrophorus electricus have been examined by studies of its interaction with structurally related, constrained aromatic bis quaternary compounds. Among the compounds synthesized was 3,3'-bis[a-trimethylammonium)-methyllazobenzene dibromide (3,3'-bisQ). This compound is photochromic and can exist in a cis or trans isomeric form, both of which have now been isolated in pure form.' Trans-3,3'-bisQ is the most potent activator known, producing a 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Bis Q (Bartels et al 1971). Models show that this compound is constrained in structure (Wassermann et al 1979) and because of its potency as an agonist we concluded that its molecular "topography" was complementary to that of the combining site of AChR. In a rather casual way, we hypothesized that the binding characteristics of antibodies raised to BisQ might mimic those of AChR.…”
Section: Early Experiments In Rabbitsmentioning
confidence: 97%
See 1 more Smart Citation
“…Bis Q (Bartels et al 1971). Models show that this compound is constrained in structure (Wassermann et al 1979) and because of its potency as an agonist we concluded that its molecular "topography" was complementary to that of the combining site of AChR. In a rather casual way, we hypothesized that the binding characteristics of antibodies raised to BisQ might mimic those of AChR.…”
Section: Early Experiments In Rabbitsmentioning
confidence: 97%
“…tran.s-i.y -bis[«-trimethy!ammonio)-methyl]azobenzene (BisQ) (Bartels ct al. 1971. Wassermann et al 1979) at a time when we were interested In photoregulating AChR activity (Erlanger 1976, Erlanger et al 1982.…”
Section: Introductionmentioning
confidence: 99%
“…Since the work of Beers and Reich (1970), considerable effort has been devoted to producing a "pharmacophore" capable of describing the structural and electronic features necessary for agonist activity at nicotinic acetylcholine receptors (e.g., Wasserman et al, 1979;Sheridan et al, 1986;Spivak et al, 1989). The overall structures of these models consist of a cationic center (e.g., the quaternary amine) and a hydrogen bond acceptor (e.g., the carbonyl oxygen), with a distance of -5.9 A between the quaternary nitrogen and the van der Waals extension of the carbonyl oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…L'isomère cis est quant à lui quasiment inactif (<1 %). Le BisQ est donc un trans agoniste ( Figure 3E) (Wassermann et al, 1979) qui a été utilisé pour photocontrôler directement et réversiblement le potentiel de membrane de l'électroplaque. Les propriétés photochimiques et structurellement contraintes du BisQ ont également été mises à profit pour définir la topologie des sites agonistes du nAChR musculaire (Wassermann & Erlanger, 1981), et notamment montrer le caractère hydrophobe de ce site (Wassermann et al, 1979).…”
Section: Photopharmacologie Des Récepteurs Nicotiniquesunclassified
“…Le BisQ est donc un trans agoniste ( Figure 3E) (Wassermann et al, 1979) qui a été utilisé pour photocontrôler directement et réversiblement le potentiel de membrane de l'électroplaque. Les propriétés photochimiques et structurellement contraintes du BisQ ont également été mises à profit pour définir la topologie des sites agonistes du nAChR musculaire (Wassermann & Erlanger, 1981), et notamment montrer le caractère hydrophobe de ce site (Wassermann et al, 1979). Des expériences de photoisomérisation flash du BisQ ont permis de faire un saut de concentration ultra-rapide en agoniste (ordre de la ms) (Nass et al, 1978 ;, et de confirmer que le nAChR musculaire a besoin de deux molécules d'agonistes pour s'activer (Sheridan & Lester, 1982).…”
Section: Photopharmacologie Des Récepteurs Nicotiniquesunclassified